Ethical and political implications of reflective practice among preservice teachers. Issue 5 (3rd September 2017) - LaBelle, Jeffrey T.
Abstract: This study investigates the ethical and political implications of reflective practice among preservice teachers. The author reviewed previous research which suggests the need for a more critical analysis of teacher education programs to implement more intensive reflective methodologies that foster authentic, caring, dispositional development as a moral obligation toward socially just practice rather than mere audited compliance with standards-based technical training. This position paper then analyzes preservice teacher education as an interdependent process of methodological development, perceptive development, and cognitive/affective development. Finally, the author makes recommendations for program modification to better prepare preservice teachers to conceptualize their transformative role in society.